Public Perceptions of Breast Implant Complications and the FDA Boxed Warning on Implants. Issue 11 (8th November 2022) - Hyland, Colby J.; Gadiraju, Goutam; Parikh, Neil; Dey, Tanujit; Broyles, Justin M.
Abstract : Background: The US Food and Drug Administration (FDA) issued a boxed warning on breast implants in October 2021, requiring communication of certain risks to patients. This study assessed how this boxed warning may impact public perceptions of breast implants. Methods: A cross-sectional survey was administered to adult women in the United States in December 2021 using Amazon Mechanical Turk to assess perceptions of breast implant risks communicated in the FDA-issued guidance. Sociodemographic predictors of responses were identified using multivariable models. Results: There were 494 complete responses. Respondents had a mean age of 36.9 years, and 80% had an associate's degree or higher. At baseline, most would consider receiving implants for reconstructive or cosmetic purposes (65%). Some were unsure or indicated that it is not possible to undergo mammograms after receiving implants (42%). After provided information in the FDA guidance, the majority strongly agreed or agreed that they were less likely to receive implants knowing the risk of anaplastic large cell lymphoma (75%), because implants contain chemicals/heavy metals (74%), and because implants are not lifetime devices (68%), with greater odds among Hispanic respondents (OR, 2.35; P < 0.01) and lower odds among higher-income respondents (OR, 0.64; P = 0.03). Conclusions: There are misconceptions with regard to breast implant-associated risks. Despite most laywomen indicating that they would consider receiving implants at baseline, the risks communicated in the 2021 FDA boxed warning may make patients less likely to receive implants, with variability among different sociodemographic populations.